Sistem Diagnosis Penyakit Tanaman Mangga Menggunakan Metode Bayesian Network - Asep Ardi Herdiyanto; Nurul Hidayat; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Diagnosis system app for mango disease is an application that aims the farmers community, especially for the mango farmers so that symptoms can be handled early. This system is built based on the problems that occur in the community, namely the difficulty in recognizing pests and diseases of mango plants. Because mango pests and diseases have quite a number of symptoms and there are similarities in symptoms that some diseases have. This is one of the causes of reduced productivity levels of mango plants in Indonesia, recorded from the 2015 Central Bureau of Statistics research that the national harvest decreased by 252 thousand tons with the total number of 2,178 thousand tons in 2015. However, in 2014 there were 2,431 million tons. The Bayesian Network method was chosen in this study because Bayesian Network includes all features in the training data, thus making this method optimal in carrying out the calculation process. This system uses the Android operating system, because Android is quite even and popular in the Indonesian smartphone market until now. The data used in this study were obtained from lecturers at the Faculty of Agriculture, Brawijaya University, Malang. The results of this study indicate that, in testing the accuracy of 32 test data get an accuracy rate of 87.5%.